Machine Repositioning for DMG Analysis Based on the Maintenance Cost - halawani, sami; M.A., Burhanuddin (IEEE, 2010)
Recent economic depression worldwide demand every department in industries to develop better control on their production cost, hence increasing company profit margin. Therefore, it is vital for maintenance department as a support team in the industries to acquire all maintenance data, to process information instantaneously, and subsequently to transform it into a useful decision. This study presents a methodology to utilize available information from failurebased maintenance. The goal of the study is to show the importance of costing analysis by describing some observation in small and medium industries. This paper demonstrates how costing analysis is conducted before fitting other variables in Decision Making Grid model. This model gives better result to categorize the machines, reduce cost and boost the earning for the manufacturing plant. The case study and experimental result shows the cost analysis in Decision Making Grid model give more promising result for real production floor in SMI. The improvement of Decision Making Grid model for decision analysis with costing analysis is recommended as useful function in Computerized Maintenance Management System.